Нормативно-правові акти як організаційний засіб досягнення завдань центральних органів виконавчої влади - Ширшикова, Р.; Shyrshykova, R. (СНУ ім. Лесі Українки, 2018)
У статті проаналізовані наявні в сучасній науці підходи до вивчення проблем, пов’язаних з необхідністю постійного вдосконалення діяльності органів державного управління, які здійснюють цілеспрямований організовуючий та координуючий влив не тільки в сфері державного управління, але й виступають основним засобом розвитку суспільства в цілому. Прийняття якісного нормативно- правового акту є однією із найбільш важливих умов ефективного існування органів державної влади. The article reveals the organizational and legal aspects of ensuring the implementation of normative legal acts by the central executive body of Ukraine. The analysis of the scientific thought about normative legal acts, definition of the concepts, essence and forms of normative legal acts of the central bodies of the executive power of Ukraine provide clues to the solution of the problem. In the focus of attention are the kinds of the normative legal acts used by the central bodies of the executive power in their activities. These acts are considered as legal fixation of the optimal management solution. The author analyzes the basic organizational and legal principles of implementation and evaluation of the effectiveness of normative legal acts of the central executive power of Ukraine.
Regulatory Legal Acts as an Organizational Tool/Means for Achieving the Objectives of the Central Executive Power Bodies
Keywords: нормативно-правовий акт; управлінський процес; організаційно-правові засади; адміністративно-правові відносини; normative-legal act; administrative/management process; organizational and legal principles; administrative-legal relations